CONVERTING AN AFN TO A AFD - Ruiz L., Edgar (2003)
This article presents the change from a non-determinist fnite automaton (AFN) into a determinist finite automaton (AFD), making use of a subset construction. The subset construction algorithm is based on the transitive closure or ? ?lock. Its implementation is done through a C++ language program, whose code and output are thoroughly presented.